Developing Open Educational Resources through Learning Design and Agile Practices - Arimoto, Maurício M.; Barroca, Leonor; Barbosa, Ellen F. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2016)
One of the current challenges related to Open Educational Resources (OERs) is how to produce quality and relevant materials to be reused and adapted to different contexts and learning situations. In this paper we present a flexible and systematic method for OERs, called AM-OER, that allows the development of OERs to evolve incrementally, and be modified and improved as needed. Practices of Learning Design are incorporated into the OERs development, making the design more understandable and shareable, and facilitating the reuse and adaptation. We applied AM-OER through a case study involving the development of a course in the software engineering domain. The results obtained suggest the applicability and usefulness of the AM-OER in the development of OERs.